Recent intensification (2004-2020) of permafrost mass-wasting in the central Mackenzie Valley foothills is a legacy of past forest fire disturbances ... - Young, Joseph M. (University of Alberta Library, 2022)
Supplemental shapefiles of mapped thaw slumps and deep-seated permafrost failures associated with "Recent intensification (2004-2020) of permafrost mass-wasting in the central Mackenzie Valley foothills is a legacy of past forest fire disturbances" ...